Comparison of Lidocaine with Lidocaine Plus Reserpine for Intravenous Regional Anesthesia in Volunteers. Issue 4 (October 1985) - Heavner, James E.; Racz, Gabor B.; Rosenberg, Per H.
Abstract : In eight volunteers, the quality of anesthesia provided when 0.5% lidocaine (3 mg/kg) was administered alone or together with reserpine (1.2-1.8 mg) for intravenous regional anesthesia was compared. There were no statistically significant differences between plasma levels of lidocaine following cuff deflation, although in most subjects (5/7) the levels were higher after lidocaine plus reserpine than after lidocaine alone. Changes in median-nerve-evoked potentials, time to loss of grip strength and perception of electrical stimulation, pin-prick and blunt probe were similar after both treatments. Recovery of motor block (grip strength) was faster after lidocaine plus reserpine than after lidocaine alone. There was no evidence that addition of reserpine resulted in sympathetic block lasting more than 24 hours. Most subjects had longlasting unpleasant side effects when reserpine was administered. These results indicate that there is no favorable cost (side effects)/benefit ratio associated with adding reserpine to local anesthetic to improve the quality of intravenous regional anesthesia.